Pengaruh Profitabilitas, Likuiditas, Solvabilitas, Aktifitas, dan Ukuran Perusahaan terhadap Harga Saham Perusahaan Infrastruktur yang terdaftar di BEI - Prasetya, Fahkriansyah Kurniawan; Wuryani, Eni (Jurnal Profiet, 2025)
This study aims to analyze the influence of five variables—profitability, liquidity, solvency, activity, and firm size—on the stock prices of infrastructure companies listed on the Indonesia Stock Exchange (BEI) during the period 2021–2023. A purposive sampling technique was applied to obtain 56 companies from secondary data. Analysis was conducted using the multiple linear regression method in order to ensure the accuracy of the research model. The results of the study indicate that ROA and DER have a significantly negative effect on stock prices. Meanwhile, CR, TATO, and Total Asset do not show a significant effect. These findings indicate that although infrastructure companies are able to generate profits, a high debt structure and potential inefficiencies in asset utilization can reduce investment interest, thereby impacting a decline in stock prices. Keywords: ROA, CR, DER, TATO, Stock Price